"A Little Bit of Their Souls": Investigating the Concept of Dignity for People Living With Dementia Using Caregivers' Blogs. (February 2021) - Anderson, Joel G.; Bartmess, Marissa; Hundt, Elizabeth; Jacelon, Cynthia
Dignity is an important component of quality of life and a core value of family nursing care. Few studies have explored dignity in community-dwelling adults with dementia. This study used blogs written by caregivers to explore the concept of dignity in dementia caregiving. A template analysis of blogs written by family caregivers of people with dementia was conducted. Four themes were defined a priori in relation to Jacelon's model of dignity: perceived value from others, self in relation to others, behavioral respect, and self-value. Caregivers wrote about experiences that related to each of the four a priori themes from Jacelon's model. In addition, the theme of dignity by proxy was derived from the analysis. By understanding the concept of dignity in the context of dementia family caregiving, interventions and services can be developed to improve family quality of life through dignifying, family-focused care.